Concurrent validity and intra-unit reliability of the Speedtrack X radar gun device for measuring tennis ball speed - Abdioglu, M.; Akyildiz, Z.; Clemente, F. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
The aim of this study was two-fold: (i) to test the concurrent validity of the Speedtrack X radar device for measuring tennis ball speed in comparison to a Pocket radar gun and (ii) to test the intra-unit reliability of the Speedtrack X radar device for measuring tennis ball speed. A total sample of 116 tennis ball throws performed by the same machine were measured in a single session. All throws were simultaneously measured by one Pocket radar device (reference criterion) and one Speedtrack X radar gun. Reliability levels were calculated using Pearson`s correlation test (r), the intra-class correlation test (ICC), and coefficient of variation (CV), while concurrent validity was tested using Bland-Altman and effect size (for measuring between-device differences). High correlation between the data obtained from the two devices was found (r = 0.932, p < 0.001). The ICC of the measurements of the data obtained from the two devices is high (r = 0.964, p < 0.001). The results allow us to conclude that the Speedtrack X radar gun is valid and reliable for measuring tennis ball speed.